Evaluasi Usability dan Perbaikan Desain Antarmuka Pengguna Aplikasi H&M - Inas Aqliya; Ismiarta Aknuranda; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
From the results of observations on the Google Play Store and initial interviews with 3 participants, it shows that users still find problems and difficulties in using the H&M application. The problems consist of application user interface problems, user experience, and slow application responses. Therefore, a usability evaluation was carried out to find out more about the problems experienced by users when interacting with the H&M application. In addition, it is also to calculate the value of the aspects of effectiveness, efficiency, and satisfaction with the H&M application. Based on the results of the problem analysis in the initial usability evaluation, the types of problems found in the form of problems with buttons, information, navigation, typography, gestures, layout, scrolling, application bars, responses, filters, reviews, item selection, checkout, status, text fields, and menu. From the analysis of the problems, it is produced 38 number of guidelines (guidelines) improvement. The results of user interface improvements in the form of mockups and prototypes that have been designed are then carried out further usability evaluations. Furthermore, the comparison of usability values ​​in the initial usability evaluation and further usability evaluation is carried out. In the aspect of effectiveness, the success rate metric has increased from 50% to 86.25%. Meanwhile, the error rate metric value decreased from 63% to 12%. In terms of efficiency, the value of the time-based efficiency metric has increased from 0.60% per second to 2.80% per second. In the aspect of satisfaction, the SUS score obtained also increased from 30.75 to 81.62.